On the Ionic Conductivity of Polymer Electrolytes in Terms of Hole Fraction - TAV, CUMALİ; YAHŞİ, UĞUR (JOHN WILEY & SONS INC, 2008)
A theoretical model to interpret the conductivity of ions through polymer electrolytes is established in terms of the temperature and pressure-dependent hole fraction computed from Simha-Somcynsky hole theory. The model successfully linearizes the logarithm of PPG and PEG conductivity data with NaCF3SO3 in a 20:1 ratio for a broad range of temperature and pressure. The conductivity parameter and transmission coefficient with an additive hole fraction constant are discussed and compared for both species. The derivative of the logarithm of conductivity with respect to the hole fraction decreases inversely with the hole fraction and saturates at about 0.08 and 0.12 hole fractions for PPG and PEG, respectively. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2249-2254, 2008
Keywords: free volume; hole fraction; ionic conductivity; modeling; PEG; polymer electrolytes; PPG; Simha-Somcynsky theory; statistical thermodynamics; voids; FREE-VOLUME THEORY; MOLECULAR-WEIGHT HYDROCARBONS; LOCAL FREE-VOLUME; GLASS-TRANSITION; VACANCY BEHAVIOR; TRANSPORT; PRESSURE; LINKING; NEED; VISCOSITY